Near-shore island lizard fauna shaped by a combination of human-mediated and natural dispersal - Salermo, Patricia (2022)
Aim: Island biotas provide opportunities to study colonization and adaptation to novel environments. Islands, especially near-shore islands, may have a long record of human habitation such that some lineages result from human-assisted introductions. Here, we combine phylogenetic analyses with fossil data and historical specimen records to reconstruct colonization histories, characterize among-island divergence and assess the role of humans in shaping the evolutionary history of lizards inhabiting a near-shore island archipelago. Location: Channel Islands and adjacent mainland of California, United States. Taxa: Western fence lizard (Sceloporus occidentalis), southern alligator lizard (Elgaria multicarinata), common side-blotched lizard (Uta stansburiana). Methods: We sequenced mitochondrial DNA (ND1, cyt-b) from each of three lizard species, covering their entire island distributions plus the adjacent mainland. For each, we estimated diversity within and among each island, obtained maximum likelihood bootstrapped phylogenies, constructed haplotype networks and tested for population expansion. We used museum specimen records and microfossil evidence to infer colonization scenarios. Results: Sceloporus occidentalis is characterized by a single island-colonization event, and exhibits the deepest divergences from mainland relatives and the highest among-island divergence. Elgaria multicarinata and Uta stansburiana each have at least three distinct colonization events, with fossil and historical data indicating that some of these occurred after humans arrived to the islands. Main Conclusions: The evolution of Channel Island lineages for two lizard taxa has been mediated by ancient and contemporary anthropogenic activity, while the evolution of the third is shaped by natural dispersal and vicariance caused by sea-level rise. Genetic divergence corroborates the treatment of S. occidentalis as an endemic island species, Sceloporus becki. The unique histories of these three taxa are synthesized with other Channel Island lineages highlighting that taxa inhabiting islands with long histories of human activity should be carefully studied to assess the role of people in facilitating colonization and subsequent gene flow.